Meningkatkan Literasi Jaringan Komputer bagi Siswa SMK TKJ: Pelatihan untuk Pemingkatan Pengetahuan dan Minat terhadap Teknologi Informasi: Improving Computer Network Literacy for TKJ Vocational School Students: Training for Knowledge and Interest in Information Technology Improvement - Barovih, Guntoro; Ajismanto, Fahmi; Yuniansyah, Yuniansyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
In the modern technological era, mastering computer network literacy is very important, especially for vocational high school (SMK) students majoring in Computer and Network Engineering (TKJ), preparing to face Industry 4.0 and 5.0. To enable students to apply basic network understanding in the workplace, they need theoretical knowledge and practical experience. This training aims to increase students' interest and understanding of computer networks using practice-based training and software simulations such as Packet Tracer and VirtualBox. The methods used include interactive material delivery, hands-on exercises, open discussions, and evaluations using pre-tests, post-tests, and interest questionnaires. The results show a significant improvement: the average pre-test score for computer network literacy, which includes components of basic knowledge, understanding of topology, and network configuration, was 43.2% and increased to 71.93% after the training, with a gain of approximately 28.73%. Besides cognitive aspects, affective aspects such as students' interest and self-confidence were also significantly enhanced. These findings support an applied and practical learning approach, essential to improve network literacy among SMK students, and emphasize the need for collaboration between education and industry to prepare a competent and ready workforce to face future technological challenges.